Empowering skills, raising awareness, and advancing crime control in South-South Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study explores non-kinetic security strategies—skill empowerment, awareness creation, and community engagement—as tools for advancing crime control in South-South Nigeria. Using a survey research design, data were collected through structured questionnaires and Key Informant Interviews (KIIs) from stakeholders, including security personnel, community leaders, and youth groups across six states. Findings reveal significant links between skill empowerment and crime control, showing how equipping individuals with marketable skillsreduces socio-economic disparities and criminal activities. Awareness creation also proves critical, fostering collaboration with law enforcement, improving crime reporting, and enhancing prevention. Grounded in strain theory, the study emphasizes the need for tailored interventions addressing regional socio-economic realities. Recommendations include expanding vocational training for vulnerable populations, integrating awareness campaigns into schools and communities, and collaborating with institutions like religious bodies and media. These strategies promote sustainable crime control, offering practical guidance for policymakers, security agencies, and community leaders.
Keywords: Empowering Skills; Raising Awareness; Crime Control; South-South Nigeria